1989
DOI: 10.1002/jcp.1041400207
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐inhibitory effect of TGF‐B on human fetal adrenal cells in primary monolayer culture

Abstract: We examined the effects of transforming-growth factor-B (TGF-B) on growth ([3H]-thymidine uptake) and function (dehydroepiandrosterone sulfate [DHAS] and cortisol production) of human fetal zone adrenal cells. Results indicate that TGF-B significantly inhibits, in a dose-related manner, both basal and epidermal growth factor (EGF)-stimulated cell growth: IC50 = 0.1-0.25 ng/ml. EGF is ineffective in overcoming the inhibitory effect of TGF-B, suggesting a noncompetitive antagonism between the two factors. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…In agreement with our findings, the peptide factor ß-transforming growth factor (ß-TGF) had no mito¬ genic effect in vitro for the fetal zone of the human fetal adrenal gland (Riopel, Branchaud, Goodyer et al 1987). However, there is evidence that the action of ß-TGF on cells is bifunctional: stimulating cell growth in certain instances, and inhibiting cell growth in others, particularly at concentrations less than 1 pg/1 (Roberts, Anzano, Wakefield et al 1985).…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with our findings, the peptide factor ß-transforming growth factor (ß-TGF) had no mito¬ genic effect in vitro for the fetal zone of the human fetal adrenal gland (Riopel, Branchaud, Goodyer et al 1987). However, there is evidence that the action of ß-TGF on cells is bifunctional: stimulating cell growth in certain instances, and inhibiting cell growth in others, particularly at concentrations less than 1 pg/1 (Roberts, Anzano, Wakefield et al 1985).…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that TGF-␤1 was able to inhibit cell proliferation (30); this seems to be achieved by the arrest of the cell cycle progression (31). In fact, we observed inhibition of proliferation (decrease in cell cycle progression speed) in human leukemic MO7e cells by TGF-␤1 (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…TGFh regulates adrenal development (22,23) and can inhibit adrenal steroid production (43,44). TGFh can act either as a tumor suppressor or promote cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…TGFh is also involved in the regulation of human fetal adrenal development. TGFh may exert an antimitotic effect on human fetal adrenal cells in vitro (22,23). Moreover, previous studies suggested an interaction between cAMP/PKA and TGFh pathways (24,25).…”
Section: Introductionmentioning
confidence: 93%